2009
DOI: 10.1177/0888406409334202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Video Models of Evidence-Based Instructional Practices to Enhance Teacher Learning

Abstract: A process was developed to create Web-based video models of effective instructional practices for use in teacher education settings. Three video models, created at three university sites, demonstrated exemplary implementation of specific, evidence-based strategies in reading, math, and science. Video models of strategies were field tested with preservice and practicing teachers working with diverse student populations. The authors provide an explanation of the video development process and present field-test d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Some of the television channels were particularly designed to manifest and display these kinds of pre-recorded videos. Video technology also can include VHS tapes, DVDs, and streamed video from Skype, Teacher Tube, You Tube, Webcams, and Adobe Connect (Diecker, Lane, Allsopp, O'Brie, Kyg, & Butler, 2009). Interactive video games can be used as a teaching tool in higher education institutes as well (White, 2009).…”
Section: Video and Audio Optionmentioning
confidence: 99%
“…Some of the television channels were particularly designed to manifest and display these kinds of pre-recorded videos. Video technology also can include VHS tapes, DVDs, and streamed video from Skype, Teacher Tube, You Tube, Webcams, and Adobe Connect (Diecker, Lane, Allsopp, O'Brie, Kyg, & Butler, 2009). Interactive video games can be used as a teaching tool in higher education institutes as well (White, 2009).…”
Section: Video and Audio Optionmentioning
confidence: 99%
“…This research serves as a solid framework for creating videos to show educational practices; our current study takes this a step further by looking at whether video can actually teach participants how to implement specific instructional strategies. Dieker et al (2009) created and field-tested three videos to model effective reading, mathematics, and science lessons to preservice and inservice teachers. The reading instruction video focused on a difficult research-based strategy to implement, Text Talk (Beck & McKeown, 2001).…”
Section: Video For Reflectionmentioning
confidence: 99%
“…Recent research findings on video in teacher preparation show the technological tool to be preferred over traditional teaching methods (Dieker et al, 2009), to boost confidence to teach (Dymond & Bentz, 2006;Friel & Carboni, 2000;Kent & Simpson, 2010), and to improve knowledge of teaching (Dieker et al, 2009). Just one study (Dieker et al, 2009) was found to examine the effect of videos modeling strategies on actual teaching ability. The current study adds to this line of research by not only measuring whether preservice teacher knowledge increases from a video modeling an effective reading strategy, but also whether preservice teachers are able to translate acquired knowledge into practice to demonstrate effective teaching.…”
Section: Video For Reflectionmentioning
confidence: 99%
See 2 more Smart Citations